Penyuluhan Tentang Malaria Pada Keluarga Penerima Manfaat Program Keluarga Harapan (KPM-PKH) Kecamatan Woyla, Aceh Barat - Iskandar, Arif; Azwar, Azwar; Ishalyadi, Ishalyadi (Universitas Teuku Umar, 2020)
Malaria is one of the endemic diseases that are often found in the tropics. This disease is caused by the plasmodium parasite and is transmitted by female Anopheles mosquitoes. The World Health Organization (WHO) estimates that around 300-500 million cases are reported each year with one million deaths occurring in developing countries. Efforts to eradicate malaria will be carried out by involving community participation through eradicating malaria-causing vectors. In this regard, it is necessary to have public awareness to practice clean living by maintaining environmental cleanliness as a form of malaria prevention efforts. The counseling was carried out aimed at increasing public knowledge about malaria and prevention efforts. The counseling method is carried out with lectures and face-to-face discussions with participants. The results of this counseling can foster public awareness, attitudes, and behavior towards malaria prevention and control. The community is expected to be able to increase awareness of malaria transmission through prevention efforts undertaken.